Pengaruh Fitur Live Streaming, Diskon Harga Dan Ulasan Produk Terhadap Keputusan Pembelian Pos Grosir Ecer (Pge) Pada Aplikasi Shopee - Cintami Ira Yuniar; Muhammad Syaifulloh; Roni Roni; Indah Dewi Mulyani (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to determine the influence of the Live Streaming Feature, Price Discounts and Product Reviews on Poss Wholesale Retail (PGE) Purchasing Decisions on the Shopee application. This research uses a quantitative approach to measure the influence of live streaming features, price discounts and product reviews on Poss consumer purchasing decisions Wholesale Retail (PGE) official store via the Shopee application with 100 respondents adopting Partial Least Sequare (PLS).The research results show T-Statistics 2.955> 1.96 and P-Values ​​0.003 < 0.05 so that H1 is accepted and it can be concluded that the live streaming feature has an influence on purchasing decisions. On the price discount indicator, the results of the research show that the significance value seen from the T-Statistics is 6.430> 1.96 and P-Values ​​0.003 < 0.05 so that H2 is accepted and it can be concluded that price discounts have a significant influence on purchasing decisions. Then for the product review indicator, the research results show that the significance value formed is smaller than α = 0.05, namely 0.000. From these results, it can be seen that T-Statistics is 5.806> 1.96 and P-Values ​​0.000 < 0.05 so that H3 is accepted and it can be concluded that product reviews have a significant influence on purchasing decisions for Official Wholesale Retailers (PGE) via the Shopee application.